2005
DOI: 10.1089/adt.2005.3.47
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a hERG Screen Using the IonWorks HT: Comparison to a hERG Rubidium Efflux Screen

Abstract: The introduction of parallel patch clamp instruments offers the promise of moderate-throughput, high-fidelity voltage clamp for drug screening assays. One such device, the IonWorks HT (Molecular Devices, Sunnyvale, CA), was evaluated and compared to conventional human ethera- go-go-related gene (hERG) patch clamp data and an alternative functional screen based on rubidium flux. Data generated by the IonWorks HT and rubidium assays were compared to determine if either offered superior predictive value compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 25 publications
0
42
2
Order By: Relevance
“…A better correlation was observed with the values obtained in the present study than with the previously reported values, which is probably due to the differences in experimental conditions such as recording solutions and voltage protocols. The underestimated IC 50 values previously often observed due to the limited time for solution exchange and the adsorption of lipophilic test compounds (Guo and Guthrie 2005;Sorota et al 2005) were not observed in the present work. Also, the range of the IC 50 values extends over six orders of magnitude of concentrations with a slope of 0.96 determined by a linear regression, close to the unity line, indicating that the dynamic range of this method is broad enough for most of the test compounds to fall into this range.…”
contrasting
confidence: 70%
“…A better correlation was observed with the values obtained in the present study than with the previously reported values, which is probably due to the differences in experimental conditions such as recording solutions and voltage protocols. The underestimated IC 50 values previously often observed due to the limited time for solution exchange and the adsorption of lipophilic test compounds (Guo and Guthrie 2005;Sorota et al 2005) were not observed in the present work. Also, the range of the IC 50 values extends over six orders of magnitude of concentrations with a slope of 0.96 determined by a linear regression, close to the unity line, indicating that the dynamic range of this method is broad enough for most of the test compounds to fall into this range.…”
contrasting
confidence: 70%
“…Typically, hERG potencies measured by automated and manual electrophysiology are in good agreement; however, some compounds are known to appear less potent when tested by automated electrophysiology. [23][24][25][26] Discrepancies typically arise from hydrophobic compounds being adsorbed to the surface of the plate used to hold the compound or to the patch plate itself. Glass-coated compound plates can help to minimize the nonspecific binding to the compound plate but come at a significant cost.…”
Section: Medium and High Throughput Herg Assaysmentioning
confidence: 99%
“…Using CHO cells that stably express hERG channels, IonWorks allows for assessment of approximately 200 data points per Patch plate and about 80 concentration-response curves per day [21][22][23][24]. A good pharmacological correlation with conventional MPC data was observed in terms of rank-order of compounds with hERG activity although the concentration-response curves were shifted to the right (within 3-to 5-fold).…”
Section: Automated Planar Patch-clamp Methodsmentioning
confidence: 98%